Developing agility and quickness (Sport Performance Series, 2012)
"Developing Agility and Quickness" focuses on improving athletes' fleetness of foot, speed of change of direction and reaction time. Applicable across almost every sport, the book explains the purposes behind the training, presents tests to gauge ability and monitor progress. "Developing Agility and Quickness" contains more than 100 drills to improve each area as well as providing programmes that develop sport-specific quickness and agility. For all athletes, the ability to quickly change direction is often the difference between success and failure. Virtually all sports require rapid whole-body movements in which an athlete is required to instantly accelerate, decelerate, or change direction in response to game situations. The reality is that in most sports the ability to quickly change direction is more important than having great straight-line sprinting speed. For this reason, many coaches and athletes are interested in finding effective ways to improve agility and quickness. The purpose of this book is to assist the sports coach, athlete, and strength and conditioning professional in accomplishing that goal.